Sistem Monitoring Capaian Pembelajaran di SMKN 1 Kota Bima Berbasis Web dan Android - Whitnu Nastain; Ikrimach Ikrimach (Jurnal Teknologi Informasi dan Multimedia, 2024)
In the process of teaching and learning, there is always a specific goal to be achieved, aiming to fulfill and produce a set of achievements targeted by a subject teacher. Each subject has different learning outcomes. Supervision of learning outcomes is necessary to ensure that both students and teachers can achieve the agreed-upon or school-established learning outcomes. Throughout this process, schools face difficulties in carrying out supervision to ensure that learning outcomes are met. This challenge underscores the need for an application that can assist in the supervision of learning outcomes, aiding schools in ensuring that both teachers and students can successfully achieve the set learning outcomes. The application development process utilizes the waterfall method, with data collection using documentation techniques. The programming languages used are Dart and PHP. The developed application includes the ability to monitor quiz scores, assignment grades, student attendance levels, as well as creating an interactive and engaging discussion forum. After implementation and testing, the application proves to be highly effective in fulfilling its function of supervising learning outcomes. In summary, during the teaching and learning process, the primary objective is to achieve the set learning outcomes. The challenges faced by schools in supervising these outcomes emphasize the necessity for an application that can facilitate this process, ensuring the successful attainment of learning goals by both teachers and students. The development process, using the waterfall method, along with Dart and PHP programming languages, results in an application with features such as quiz and assignment monitoring, attendance tracking, and an interactive discussion forum. The successful implementation and testing demonstrate the application's effectiveness in supervising learning outcomes, providing a practical and efficient solution for schools to monitor and enhance the quality of education.